Chronic kidney disease-associated pruritus: features and associated factors - Hasan, Intisar Ahmed; Obeed, Rana Khalid (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2023)
Introduction: Chronic kidney disease (CKD) is a condition characterized by a gradual loss of kidney function over time due to injured kidneys or when the glomerular filtration rate is less than 60mL/min/1.73 m2, for more than three months. The final stage of renal illness is the deadly stage of severe CKDs, and its occurrence has increased in the previous 30 years. Chronic kidney disease-associated pruritus is an undesirable condition that triggers itching and negatively affects sleep quality. The study aims to evaluate the features of Pruritus associated with CKD and its association with sociodemographic variables. Method: Cross-sectional study of 53 patients with chronic kidney disease collected from Baqubah dialysis center from the period of April 1st, 2020, to September 1st, 2020, inclusion criteria are all patients with chronic kidney disease who suffer from rashes and Pruritus while exclusion criteria are all patients suffer from rashes and Pruritus does not associate to CKD and cause by other conditions. All patients reported their sociodemographic data like age, gender, sleep pattern, the severity of disease, negative affection of sleep quality and location of Pruritus. Results: CKD-associated Pruritus were distributed as follows: of all patients, age 52±6 years old; 83% were 45 years and above and 13% with age 45 years old and below .23% of patients were females and 77% males, in 40% of patients’ Pruritus interfered with their sleep while 60% not. About 40% of patients with pruritic are severe, while 60% of them are not. 62% of pruritic patients occur in the trunk, while 38% occur in the entire body. There was a significant association between the severity of Pruritus with gender, the affected area, and sleep. Conclusion: Utmost communal symptom of skin in ESRD is Pruritus, broadly identified as “uremic pruritus.” Due to there is no correct association with uremia, significant association occur in male, age higher than 45 years, interferes with sleep and predominates in the trunk region.